Gabby solved x2 - 3x = 4 as shown below:
x2 - 3x - 4 = 0
(x - 4)(x + 1) = 0
x = -4 and x = 1

Caitlyn says Gabby is wrong and believes this is the solution:
x2 - 3x - 4 = 0
(x - 4)(x + 1) = 0
x = 4 and x = -1

Is Gabby or Caitlyn correct?  What mistake was made by the incorrect girl?  Type your response in the box provided. 

Respuesta :

Caitlyn is correct.
Both factored correctly but the reason Gabby is wrong is because of the Zero Product Property, which says if (x-4)(x+1)=0, then (x-4)=0 or (x+1)=0.

If (x-4)=0, then the value of x must be 4.
If (x+1)=0, then the value of x must be -1.